Preparation and characterization of monomodal grapevine virus a capsid protein - Santana, Vinícius S.; Mariutti, Ricardo B.; Eberle, Raphael J.; Ullah, Anwar; Caruso, Icaro P.; Arni, Raghuvir K. [UNESP] (My University, 2015)
Grapevine virus A (GVA), a flexible filament of approximately 800 nm in length is composed of capsid subunits that spontaneously assembles around a positive sense genomic RNA. In addition to encapsidation, plant viruses capsid proteins (CPs) participate in other processes throughout infection and GVA CP is involved in cell-to-cell translocation of the virus. A protocol was developed to obtain low-molecular weight GVA-CP that is not prone to aggregation and spontaneous assembly and this was characterized by circular dichroism and dynamic light scattering. These results indicate the suitably of GVA-CP for X-ray crystallographic and NMR studies that should lead to the elucidation of the first three-dimensional structure of a flexible filamentous virus from the Betaflexiviridae family.